EFEKTIVITAS Glomus clorum TERHADAP PERTUMBUHAN TANAMAN CABAI RAWIT (Capsicum frutescens L.), TOMAT (Solanum lycopersicum L.) DAN TERUNG (Solanum melongena L.) - Khairun Nisa; Yusran; Wahyu Harso (Biocelebes, 2020)
Increasing plant growth by arbuscula mycorrhizal fungi depends on the fungus and plant spesies. The aim of this study was to determine the efectivity of fungal mycorrhizal fungus on the growth of cayenne pepper, tomato and eggplant which are Solanaceae family members. The study was conducted by Completely Randomized Design method.with two factors. The fisrt factor was species of experimental plant consisted of cayenne pepper (Capsicum frutescens L.), tomato (Solanum lycopersicum L.) and eggplant (Solanum melongena L.). The second factor was addition of Glomus clorum inokulum consisted of with and without inoculum addition. The result showed that there was no effect of inoculum addition on plant growth of three experiemal plants. The quality of inoculum used for this experiment was not good enough furthermore fungi could not germinate and colonize plant root.